Akhlak Mahmudah Perspective of Ibn Miskawaih - Arroisi , Jarman; Ussisa ‘alat Taqwa; Ahmad Farhan Nasution (Jurnal Spiritual Healing, 2024)
The moral of Mahmudah is an important point in the tradition of Islamic thought that has been explained in depth by the Islamic philosopher Ibn Miskawaih. According to him, mahmudah morality refers to the noble and noble qualities that individuals strive for to achieve happiness and peace in life in this world and the hereafter. This study analyzes good behavior in Islamic psychology from the point of view of Ibn Miskawaih. In this study, the author used Library Research and used descriptive methods of analysis to understand Ibn Miskawaih's views on good behavior. According to Islamic psychology, individual behavior is influenced by mental and psychological aspects. Analysis of behavioral treatment in Islamic psychology shows that the concept of mahmudah morality plays an important role in shaping human behavior. The results of Ibn Miskawaih's Akhlak mahmudah are divided into several points: First, Encourage humans to behave well, Second, establish good relationships with humans, and Third, Build strong character through good character can help individuals overcome the challenges of daily life and Fourth, maintain balance in various aspects of life.